2016
DOI: 10.1186/s12913-016-1475-6
|View full text |Cite
|
Sign up to set email alerts
|

Causes of cancellations on the day of surgery at a Tertiary Teaching Hospital

Abstract: BackgroundCancellation of elective scheduled operations on the day of surgery leads to an inefficient use of operating room (OR) time and a waste of resources. It also causes inconvenience for patients and families. Moreover, day of surgery (DOS) cancellation creates logistic and financial burden associated with extended hospital stay and repetitions of pre-operative preparations as well as opportunity costs of lost time and missed income. The objective of this study is to establish the rate of elective surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
3
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 25 publications
11
93
3
14
Order By: Relevance
“…The incidence of elective surgical cancellations has been reported in the literature to range from 1.87% to 40%. 1,11,18 The total cancellation rate was 21.9% in our study, comparable to the rate found by Chaylia et al 18 in Tanzania, which was 21%. The high rate of cancellation in our study may be partly due to including all surgical specialties.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The incidence of elective surgical cancellations has been reported in the literature to range from 1.87% to 40%. 1,11,18 The total cancellation rate was 21.9% in our study, comparable to the rate found by Chaylia et al 18 in Tanzania, which was 21%. The high rate of cancellation in our study may be partly due to including all surgical specialties.…”
Section: Discussionsupporting
confidence: 80%
“…Mutwali et al 22 found that 68.3% were patient-related and then anaesthesia decisions (33.3%). Other authors 1,26,27 found that work-up and/or medical issues were the most common causes for DOS cancellation.…”
Section: 5 11 22-24mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the introduction of POM telehealth services, the last‐minute cancellation rate at our hospital for outreach patients was reported to be as high as 10% . Worldwide last‐minute cancellation rates are highly variable and are estimated to be between 1.96 and 24% . Our low cancellation rate is attributable to the highly selected group of patients who were assessed to be suitable and optimised for surgery by a team of experienced clinicians.…”
Section: Discussionmentioning
confidence: 93%
“…Similar findings have been reported in previous studies. Kaddoum et al showed that patients with multiple medical comorbidities were more likely to be cancelled on the day of surgery as they were not identified preoperatively for optimisation . Therefore, a thorough preoperative assessment for patients with multiple medical comorbidities can prevent a last‐minute cancellation.…”
Section: Discussionmentioning
confidence: 99%